2014
DOI: 10.1016/j.ijchv.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

A decade of complex fractionated electrograms catheter-based ablation for atrial fibrillation: Literature analysis, meta-analysis and systematic review

Abstract: Background: It has been a decade since the complex fractionated atrial electrograms (CFAEs) were first established following the publication of Nademanee's standards. However, the status and focus of CFAE research are unclear, as is the efficacy of additional CFAE ablation in atrial fibrillation (AF). This literature review and metaanalysis were designed to determine the status of CFAE research and the efficacy and complications of CFAE ablation alone, pulmonary vein isolation (PVI) alone and PVI plus CFAE abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
0
7
0
2
Order By: Relevance
“…A number of sources are said to be responsible for fractionation, with the local collision of multiple wavelets, local re-entry and zones of slow conduction said to result in EGM fractionation during AF (de Bakker and Wittkampf, 2010 ; Waks and Josephson, 2014 ). Consequently, it is thought that there is some relationship between CFAE and the maintenance of AF (Waks and Josephson, 2014 ), thus CFAE mapping and CFAE guided ablation have previously been explored (Nademanee et al, 2004 ; Nademanee and Oketani, 2009 ; Berenfeld and Jalife, 2011 ; Hayward et al, 2011 ; Li et al, 2011 ; Chen et al, 2014 ). Though both CFAE and entropy aim to capture the qualitative property of signal fractionation to some degree, entropy is differentiated from CFAE by having a quantitative definition rooted in signal processing and mathematics, and does not use empirically derived definitions.…”
Section: Information Theory and The Intracardiac Electrogrammentioning
confidence: 99%
“…A number of sources are said to be responsible for fractionation, with the local collision of multiple wavelets, local re-entry and zones of slow conduction said to result in EGM fractionation during AF (de Bakker and Wittkampf, 2010 ; Waks and Josephson, 2014 ). Consequently, it is thought that there is some relationship between CFAE and the maintenance of AF (Waks and Josephson, 2014 ), thus CFAE mapping and CFAE guided ablation have previously been explored (Nademanee et al, 2004 ; Nademanee and Oketani, 2009 ; Berenfeld and Jalife, 2011 ; Hayward et al, 2011 ; Li et al, 2011 ; Chen et al, 2014 ). Though both CFAE and entropy aim to capture the qualitative property of signal fractionation to some degree, entropy is differentiated from CFAE by having a quantitative definition rooted in signal processing and mathematics, and does not use empirically derived definitions.…”
Section: Information Theory and The Intracardiac Electrogrammentioning
confidence: 99%
“…Recent meta-analyses [3,36] report that 77% of the ablation-treated patients are asymptomatic at a 1-year follow-up, in comparison to 52% of medically treated patients. It should be noted that up to a third of patients requires a 2 nd ablation (redo-ablation) to achieve a long-lasting symptom-free life [3,4,23,25,38]. We still lack enough information to personalize ablation in each individual, which could results in more efficacious and less extensive ablation in some patients [39].…”
Section: Electrophysiological Options To Achieve Sinus Rhythmmentioning
confidence: 99%
“…CFAE definition does not distinguish between different morphologies; consequently, fractionated EGM according with CFAE definition are not necessarily related to arrhythmogenic substrates. Moreover, several studies have shown conflicting results with Nademanee [56,59]. This may lead the electrophysiologist to confuse the fractionated EGM that are functional in nature [60] with fractionated EGM corresponding to arrhythmogenic sources, leading to incorrect target sites for ablation.…”
Section: Introductionmentioning
confidence: 99%